Evaluasi Pelaksanaan Program Usaha Kesehatan Gigi Sekolah (UKGS) Di SDN 212 Harapan Kota Bandung - Ahdiansyah, Balqis Shafa'; Fatikhah, Nurul; Praptiwi, Yenni Hendriani; Utami, Ulfah (Poltekkes Kemenkes Bandung, 2024)
The School Dental Health Program (UKGS) at SDN 212 Harapan in Bandung aims to maintain students' dental health through promotive, curative, and preventive activities but was halted in 2019 due to the COVID-19 pandemic. This study evaluates the program's implementation at SDN Harapan 212 using a descriptive, qualitative approach with in-depth interviews, observations, and documentation. Data were analyzed through transcription, reduction, presentation, and verification. Findings reveal deficiencies in input, such as a lack of human resources (dentists and little dentist) and suboptimal facilities (non-functioning dental units). The organizational structure of UKS/UKGS is not displayed, and there is no parental financial support. In the process, the health center's UKGS program has been halted since 2019, and curative programs are not implemented. Policies like health center SOPs and cooperation MOUs are outdated. However, the program has increased students' understanding of dental care and their independence in maintaining dental hygiene. The study concludes that the UKGS program's implementation is inadequate in terms of input and process. It provides valuable insights for improving the UKGS program in other schools and contributes to the literature on school dental health programs.